2022
DOI: 10.1186/s12872-022-02532-w
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial dysfunction may precede left atrial enlargement and abnormal left ventricular longitudinal function: a cardiac MR feature tracking study

Abstract: Background The role of the dysfunction of left atrium in the occurrence and development of cardiovascular disease has been gradually recognized. We aim to compare the impact on left atrial (LA) function between patients with hypertrophic cardiomyopathy (HCM) and hypertension (HTN) without LA enlargement using cardiovascular magnetic resonance feature tracking (CMR-FT), and if possible, explore the capability of LA function for providing clinical implication and predicting clinical adverse event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 47 publications
(64 reference statements)
4
20
0
Order By: Relevance
“…Left atrial strain is signi cantly impaired in both AMI and CMI. It is in agreement with Zhou D's [37] study suggesting that LA deformation-related damage may manifest even sooner than the LV strain in the MI. This result demonstrated that in those individuals, LV strain was not the most reliable parameter for identifying early damage.…”
Section: Discussionsupporting
confidence: 91%
“…Left atrial strain is signi cantly impaired in both AMI and CMI. It is in agreement with Zhou D's [37] study suggesting that LA deformation-related damage may manifest even sooner than the LV strain in the MI. This result demonstrated that in those individuals, LV strain was not the most reliable parameter for identifying early damage.…”
Section: Discussionsupporting
confidence: 91%
“…LA strain could be a promising biomarker to survey early diastolic dysfunction. 23 Similarly, previous studies had revealed that LA strain could be initiated before clinically apparent LVH in hypertensives. 24 , 25 This may propose an early distinctive abnormal hemodynamics of diastolic function, and hence, we can speculate that DLVOTO may ultimately induce LV diastolic heart failure which could explain the exertional dyspnea in such patients.…”
Section: Discussionmentioning
confidence: 83%
“…Second, HCM patients may experience progressive LA remodeling and dysfunction [ 34 ]. However, some studies have shown significant differences between HCM patients and healthy control subjects for LA GLS reservoir and conduit, but not LA GLS booster [ 18 , 23 , 35 ]. One possible explanation for this difference is that the preserved LA pumping function is a compensatory mechanism to maintain the stroke volume and left ventricular filling in mild diastolic insufficiency, and its deterioration reflects LA compliance in the "decompensated" phase [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the three phases of LA strain were not subdivided in this study. Zhou et al [ 23 ] used standard CMR-FT two-chamber, three-chamber, and four-chamber views to assess adverse outcomes in HCM patients. It was shown that LA reservoir strain and booster strain were associated with adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%